2015
DOI: 10.3758/s13415-015-0396-x
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic appreciation of poetry correlates with ease of processing in event-related potentials

Abstract: Rhetorical theory suggests that rhythmic and metrical features of language substantially contribute to persuading, moving, and pleasing an audience. A potential explanation of these effects is offered by Bcognitive fluency theory,^which stipulates that recurring patterns (e.g., meter) enhance perceptual fluency and can lead to greater aesthetic appreciation. In this article, we explore these two assertions by investigating the effects of meter and rhyme in the reception of poetry by means of event-related brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 70 publications
(82 reference statements)
5
51
1
Order By: Relevance
“…Thus, the enhanced P3b response to Cynghanedd appears to indicate a kind of attentional orienting response, specifically when both the stress pattern and consonantal repetition rules are observed, thus making this particular sentence a target. This is congruent with recent electrophysiological evidence showing that lyrical stanzas that contain consistent meter and rhyme facilitate processing compared with those that contain only one, or neither of these patterns (Obermeier et al, 2016). Another recent study has shown that electrophysiological responses to poetry can be modulated by prosodic elements (e.g., rhyme) alone (Chen et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, the enhanced P3b response to Cynghanedd appears to indicate a kind of attentional orienting response, specifically when both the stress pattern and consonantal repetition rules are observed, thus making this particular sentence a target. This is congruent with recent electrophysiological evidence showing that lyrical stanzas that contain consistent meter and rhyme facilitate processing compared with those that contain only one, or neither of these patterns (Obermeier et al, 2016). Another recent study has shown that electrophysiological responses to poetry can be modulated by prosodic elements (e.g., rhyme) alone (Chen et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Recall that participants were unable to overtly identify the Cynghanedd forms, and we found no correlation between reaction times and P3b mean amplitudes, contra previous findings (Conroy and Polich, 2007; Ramchurn et al, 2014; but see McCarthy and Donchin, 1981). Thus, whereas previous studies have shown that the explicit, aesthetic appreciation of poetry can be linked to implicit responses (e.g., Jacobs, 2015; Obermeier et al, 2016), the current findings provide the first tangible evidence that this link is permeable: our participants were able to implicitly detect correct poetic forms, even though they could not explicitly differentiate between conditions (cf. Renault et al, 1989).…”
Section: Discussioncontrasting
confidence: 77%
“…These include behavioral observations in field studies or in the lab (e.g., eye movements, time spent in a specific location, viewing or reading time, preferences for specific environments, movement speed and pattern) and physiological measures (e.g., facial muscle activity, pupillary dilation, patterns of brain activation, chills/goosebumps, skin conductance, heart rate, respiration rate, or body temperature). Prior studies have revealed connections of self-reported aesthetic emotions with behavioral and physiological measures (see, e.g., [217] for music and film, [218] for visual art, [92] for museum exhibitions, and [219] for poetry). The A esthemos can help increase our knowledge of whether specific aesthetic emotions are more closely linked to a specific objective measure than others.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Willems and Jacobs (2016) argue that studying processes of immersion and aesthetic appreciation requires a thorough understanding of the linguistic finesses of stories. These finesses include metric, phonological, morpho-syntactic, and semantic features at the sublexical, lexical, interlexical, and supralexical levels of discourse (Jacobs, 2015a; Jacobs et al, 2016b). …”
Section: Multidimensional Linguistic Cues Frameworkmentioning
confidence: 99%